2013
DOI: 10.1109/tns.2013.2243753
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics and Fast Neutron Response of Semi-Insulating Bulk Silicon Carbide

Abstract: Abstract-The electrical characteristics and fast neutron response of a High Temperature Chemical Vapour Deposition (HTCVD) grown semi-insulating bulk SiC wafer has been measured. Current -Voltage measurements demonstrated a low leakage current in the region of 10 -10 to 10 -12 A with a bulk resistivity of at least 10 12 -10 13 Ω.cm. Alpha particle spectroscopy measurements demonstrated an electron charge collection efficiency of up to 90% with reasonable reproducibility of the acquired spectra. Evidence of (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The best measure of the drift constant µτ scat in 4H-SiC (the only polytype for which detailed studies are available) was found to be µτ scat ∼ 3 × 10 −4 cm 2 /V, and for a saturation drift field of 8 kV/cm, we find a maximum drift length D ∼ 2.4 cm [65]. While this does imply full charge collection for devices up to 1 cm thick, the very high voltages required are likely to induce some measure of charge breakdown, despite the very high dielectric strength of SiC.…”
Section: Charge Collectionmentioning
confidence: 79%
See 3 more Smart Citations
“…The best measure of the drift constant µτ scat in 4H-SiC (the only polytype for which detailed studies are available) was found to be µτ scat ∼ 3 × 10 −4 cm 2 /V, and for a saturation drift field of 8 kV/cm, we find a maximum drift length D ∼ 2.4 cm [65]. While this does imply full charge collection for devices up to 1 cm thick, the very high voltages required are likely to induce some measure of charge breakdown, despite the very high dielectric strength of SiC.…”
Section: Charge Collectionmentioning
confidence: 79%
“…The only studies to demonstrate near full charge collection in SiC are Refs. [21,32,65], which all study energy deposition in thin films (∼40 µm). Studies of depositions in a ten times larger detector volume in e.g.…”
Section: Charge Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cubic polytype of SiC (3C-SiC) can be used as a structural material, particularly in harsh environments, due to its high hardness and strength, and good thermal shock resistance and corrosion resistance [1,2,3]. Generally, SiC bulks are densified using method such as pressureless sintering, spark plasma sintering, and liquid-phase sintering with additives (Al 2 O 3 , AlN, B, C, and B 4 C) [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%